Development of an android mobile application voice to text embedded by implementing concept of 7d-bim (facilities management) - Ahmad AlQurtubi Alkharib Shah (2022)
Currently, there is a lack of mobile applications that have been developed to allow professionals, especially building managers and owners in the construction industry to help track important asset data such as its status and maintenance manuals. Due to this, professionals such as engineers sometimes find it hard to optimize assets and carry out operations and facility management. Hence, this 7D-BIM with facilities management mobile application will be developed to provide a unique approach where everything related to the facility management process is collated at a single place within the building information model with speech-to-text recognition system, therefore, the user also can store and edit information about their facilities information in this application which is gathered to produce document and form. This study aims to study how ready the Malaysian construction industry is for Speech-to-Text Recognition (STR) implementation, as well as the challenges, benefits, and possible strategies for using STR in the Malaysian construction industry. It also focuses on developing an android app that implement the concept of 7D-BIM ( Facilities Management). A questionnaire survey of this study is conducted to 30 professional industrial players in Malaysia. Based on the survey, the rate of the readiness of STR implementation in Malaysian construction industry can be rated at 43.33%. The study also resulted to four main challenges of the adaptation; economic challenges, social challenges, technology challenges, and environmental challenges. Advantages suggested based on the survey is improve pronunciation utterance, adaptability to current technology, productivity improvement, reduce workload, and short time for documentation. The result and findings show how the mobile application were designed and developed by implementing the concept of 7D-BIM ( Facilities Management) with voice-to-text embedded system using Android Studio (IDE) software.